Enhancing compatibility and biodegradability of polylactic acid/biomass composites through torrefaction of forest residue - June-Ho Choi; Myeong Rok Ahn; Chae-Hwi Yoon; Yeon-Su Lim; Jong Ryeol Kim; Hyolin Seong; Chan-Duck Jung; Sang-Mook You; Jonghwa Kim; Younghoon Kim; Hyun Gil Cha; Jae-Won Lee; et al. (Journal of Bioresources and Bioproducts)
This study investigated the effects of torrefaction on forest residue (FR) and its subsequent application as a bulk-loading filler in polylactic acid (PLA) composites. Torrefaction enhanced the chemical properties of FR, improving its compatibility with PLA, and the crystallinity increased from 24.9% to 42.5%. The process also improved the hydrophobicity of PLA/biomass composites, as demonstrated by the water contact angle of 76.1°, closely matching that of neat PLA (76.4°). With the introduction of 20% modified biomass properties after torrefaction treatment, the tensile strength of PLA/biomass composite increased from 58.7 to 62.3 MPa. Additionally, the addition of torrefied forest residue (TFR) accelerated biodegradation by increasing the onset of degradation and inhibiting crystallization. After 90 d, the biodegradability of PLA/biomass composites reached 94.9%, which had a 6.9% increase compared to the neat PLA (88.8%). Overall, this study highlights the potential of torrefaction in enhancing both the physical properties and biodegradability of PLA-based composites, contributing to a more sustainable approach to reducing plastic pollution.